Implementation Of Non Conviction Based Asset Forfeiture (NCBAF) in Efforts to Recover Assets Resulting from Corruption in The Oil Palm Planatation Sector in Indonesia - Maydika Ramadani; Reda Manthovani; Watcharee Ariyamang (Journal Evidence Of Law, 2025)
Law enforcement in Indonesia's oil palm plantation sector faces various challenges, especially in terms of recovering assets resulting from corruption and environmental damage. Legal systems that rely on conviction-based asset forfeiture mechanisms are often slow and difficult to prove the origin of assets, thus incapable of reaching the full extent of the large ecological and economic losses. This journal examines the potential application of the Non-Conviction Based Asset Forfeiture (NCBAF) mechanism as a faster and more effective alternative solution, especially in the case of corporations with complex ownership structures and illegal land conversion modes. Through jurisprudence analysis and regulatory studies, it was found that legal reform was needed, including amendments to the Asset Forfeiture Bill and clarification of legal phrases related to state losses, so that the asset recovery system can run more fairly and efficiently. This approach is expected to strengthen efforts to eradicate corruption and environmental damage, as well as support the overall recovery of state losses in Indonesia's oil palm plantation sector.